Pro SQL Server 2008 Policy-Based Management - Simmons, Ken; Stasiuk, Colin; Segarra, Jorge (Apress : Imprint: Apress, 2010)
Pro SQL Server 2008 Policy-Based Management is critical for database administrators seeking in-depth knowledge on administering servers using the new policy-based management features introduced in SQL Server 2008. This book will cover everything from a basic introduction to policy-based management to creating your own custom policies to enforce consistent rules across your organization. Provides in-depth treatment of policy-based management in a single source Provides practical usage scenarios for policy-based management Provides guidance to help meet growing regulatory compliance needs.